Expert Consensus on the Nutrition Care Process in Guatemalan Hospitals: Findings from a Delphi Study of nutritionDay 2022 Participants - Karen Girón; Isabel Chinchilla; Christa Gómez; Marietta Lau; María René Oroxon; Elena Díaz; Jorge Gramajo; Abraham Monroy; Arlen Carrera; Massiel Roldán; Cristina Nárez; Ana Verónica Monterroso; et al. (MDPI AG, 2025)
Background: Disease-related malnutrition (DRM) remains an underdiagnosed condition in Latin American hospitals, with substantial clinical and economic consequences. The global nutritionDay initiative, promoted by ESPEN, provides a standardized audit to evaluate and improve hospital nutritional care. This study aimed to develop expert consensus recommendations to optimize the nutritional care process in Guatemalan hospitals, based on the findings from nutritionDay 2022. Methods: A modified Delphi study was conducted, including three meetings held before and after each round to discuss the results. Sixteen clinical nutrition professionals from eleven hospitals participated. A total of 89 items were assessed, with a predefined consensus threshold of 70%. Data were analyzed using R software (version 4.5.0) and Kendall’s W coefficient was applied to evaluate inter-round agreement. Results: Consensus was achieved for 51 key recommendations covering nutritional screening, clinical assessment, anthropometry, body composition, functional assessment, biochemical monitoring, dietary intervention, and post-discharge follow-up. The proposed actions are aligned with international guidelines (ESPEN, ASPEN, GLIM) and adapted to the Guatemalan healthcare context. Conclusions: This consensus provides a comprehensive and context-specific framework for standardizing and improving hospital nutritional care in Guatemala and similar settings. Its implementation could help reduce DRM prevalence and foster the development of quality indicators and digital tools for clinical nutrition management.